Prevalence and factors associated with left ventricular dysfunction in the EULAR Scleroderma Trial and Research group (EUSTAR) database of patients with systemic sclerosis. Issue 01 (10th March 2009) - Allanore, Y; Meune, C; Vonk, M C; Airo, P; Hachulla, E; Caramaschi, P; Riemekasten, G; Cozzi, F; Beretta, L; Derk, C T; Komócsi, A; Farge, D; et al.
Abstract : Objectives: To measure the prevalence of, and factors associated with, left ventricular (LV) dysfunction in systemic sclerosis (SSc). Methods: The EUSTAR database was first searched. A case-control study of a patient subset was then performed to further identify independent factors associated with LV dysfunction by simple and multiple regression. Results: Of 7073 patients, 383 (5.4%) had an LV ejection fraction (EF) of <55%. By multiple regression analysis, age, sex, diffuse cutaneous disease, disease duration, digital ulcerations, renal and muscle involvement, disease activity score, pulmonary fibrosis and pulmonary arterial hypertension were associated with LV dysfunction. In the second phase, 129 patients with SSc with LVEF <55% were compared with 256 patients with SSc with normal LVEF. Male sex (OR 3.48; 95% CI 1.74 to 6.98), age (OR 1.03; 95% CI 1.01 to 1.06), digital ulcerations (OR 1.91; 95% CI 1.05 to 3.50), myositis (OR 2.88; 95% CI 1.15 to 7.19) and use of calcium channel blockers (OR 0.41; 95% CI 0.22 to 0.74) were independent factors associated with LV dysfunction. Conclusion: The prevalence of LV dysfunction in SSc is 5.4%. Age, male gender, digital ulcerations, myositis and lung involvement are independently associated with an increased prevalence of LV dysfunction. Conversely, the use of calcium channel blockers may be protective.